Relationship Between the Behavior and Diet of Chronic Kidney Failure Patients at Johor Health Center - Sihaloho, Roy Wilson (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2023)
Chronic renal failure is a clinical syndrome caused by the annual reduced renal function, progressively and generally irreversible. Renal failure has GFR (Glomerulus Filtration Rate) < 15 ml/minutes needed therapy for change the function of renal. The effective of act as therapy for renal failure is hemodialysis. For undergo hemodialysis to manage diet is very important caused prevent progressively and generally irreversible. The knowledge of patient about diet is significantly required during to the patient is undergoing to diet so can do well for keep balancing in the renal so do its function. This research have purpose to know the correlation between knowledge of the chronic renal failure patients do hemodialysis about diet with compliance of the patient to do chronic renal failure diet in the Puskesmas Johor in 2022. Sample in this studi are 31 respondents who participated in this this study with used purposive sampling. The result of the study showed that there is a correlation between knowledge of the chronic renal failure patients can do hemodialisys about diet with compliance of the patient to do chronic renal failure diet in which p < 0.05, and the correlation is significant. It is indicated by the coefficient r = 0.494.